2022
DOI: 10.3389/fsurg.2022.968199
|View full text |Cite
|
Sign up to set email alerts
|

Application of three-dimensional (3D) reconstruction in the treatment of video-assisted thoracoscopic complex segmentectomy of the lower lung lobe: A retrospective study

Abstract: BackgroundAn increasing number of lung ground-glass nodules (GGNs) have been detected ever since low-dose computer tomography started growing in popularity. Three-dimensional (3D) reconstruction technology plays a critical role in lung resection, especially in segmentectomy. In this study, we explore the role of 3D reconstruction in thoracoscopic complex segmentectomy of lower lung lobe.MethodsA total of 97 patients who underwent complex segmentectomy of lower lung lobe from January 2021 to March 2022 were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Results from multiple, primarily retrospective, comparative studies in patients operated on for a variety of pulmonary diseases, confirm this hypothesis, although the quality of evidence is debatable due to their retrospective nature ( Table 1 ). In these studies, 3D-imaging is associated with shorter operating times ( 22 , 36 , 37 , 44 46 ), more extensive mediastinal lymph node dissection ( 23 , 36 ), a reduction in stapler reloads ( 44 ), reduced air loss on postoperative days 1–3 ( 44 ) and decreased intraoperative blood loss ( 36 ). No significant difference in other surgery-related parameters was found, such as length of hospital-stay, overall recovery, incidence of other postoperative complications and residual pulmonary function ( 22 , 23 , 36 , 44 , 45 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from multiple, primarily retrospective, comparative studies in patients operated on for a variety of pulmonary diseases, confirm this hypothesis, although the quality of evidence is debatable due to their retrospective nature ( Table 1 ). In these studies, 3D-imaging is associated with shorter operating times ( 22 , 36 , 37 , 44 46 ), more extensive mediastinal lymph node dissection ( 23 , 36 ), a reduction in stapler reloads ( 44 ), reduced air loss on postoperative days 1–3 ( 44 ) and decreased intraoperative blood loss ( 36 ). No significant difference in other surgery-related parameters was found, such as length of hospital-stay, overall recovery, incidence of other postoperative complications and residual pulmonary function ( 22 , 23 , 36 , 44 , 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, 3D-imaging is associated with shorter operating times ( 22 , 36 , 37 , 44 46 ), more extensive mediastinal lymph node dissection ( 23 , 36 ), a reduction in stapler reloads ( 44 ), reduced air loss on postoperative days 1–3 ( 44 ) and decreased intraoperative blood loss ( 36 ). No significant difference in other surgery-related parameters was found, such as length of hospital-stay, overall recovery, incidence of other postoperative complications and residual pulmonary function ( 22 , 23 , 36 , 44 , 45 ). Furthermore, there is evidence from multiple studies that preoperative 3D-imaging aided in selection of the appropriate surgical entry site tailored to the individual patient by taking their specific anatomy into account, resulting in less perioperative switching in surgical approach and lower conversion rates ( 36 , 47 , 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…Arjomandi Rad et al described the role of augmented reality in reducing preoperative planning time and workload, helping surgeons to perform complex procedures more safely by facilitating the understanding of patient-specific anatomy and anatomical variations (24). The use of a 3D reconstruction can provide a safer intervention, in terms of less intraoperative complications (e.g., vascular or parenchymal tear or inappropriate resection), reduced operative time and improved carcinologic margins (25). Creation of 3D printable models and virtual 3D reconstructions may also be used, not only as a teaching support for medical students and young residents, but also for the patient, to clarify surgery and the extent of the procedure.…”
Section: Augmented Reality: Toy or Tool?mentioning
confidence: 99%
“…Kanzaki et al performed multisubsegmentectomies, such as right S 2 b + S 3 a, left S 1+2 a + b, or others, using VATS in 11 patients using a virtual 3D pulmonary model with CTTRY, a custom software they developed, and reported that all the patients had negative surgical margins [35]. Wang et al compared 92 cases of VATS complex segmentectomy divided into 42 cases in the 3D group and 55 in the routine group and reported that all the cases in the 3D group, in which preoperative 3D-CT reconstruction was performed, had adequate surgical margin of >2 cm [36]. Iwano et al defined the virtual safety margin as a sphere extending 2 cm outside the tumor in preoperative 3D-CT simulation and reported that no positive surgical margin was achieved in all 17 primary lung cancers in 16 patients after segmentectomy [37].…”
Section: D-ct Simulation For Clinical Case Seriesmentioning
confidence: 99%
“…The use of preoperative 3D simulation led to better outcomes in many matters, including less intraoperative bleeding and chest tube duration [25], shorter operation time [26], fewer stapler reloads, and the reduction of postoperative air leakage on postoperative days 1-3 [36] compared to the cases without 3D simulation.…”
Section: D-ct Simulation For Clinical Case Seriesmentioning
confidence: 99%